Frontiers of justice : disability, nationality, species membership - Nussbaum, Martha C. (Martha Craven), 1947- (London : The Belknap Press, 2006)
The idea of the social contract is one of the most powerful approaches to social justice in the Western tradition. Exploring the limitations of the social contract, Nussbaum devises an alternative theory based on the idea of capabilities as an approach to social co-operation
Social contracts and three unsolved problems of justice -- Disabilities and the social contract -- Capabilities and disabilities -- Mutual advantage and global inequality : the transnational social contract -- Capabilities across national boundaries -- Beyond "compassion and humanity" : justice for nonhuman animals -- The moral sentiments and the capabilities approach
Includes bibliographical references and index
Keywords: Social justice; People with disabilities -- Civil rights; Minorities -- Civil rights; Animal rights; Animal Rights; Disabled Persons; Ethnicity; Social Justice